AKTUALISASI AJARAN GURU BHAKTI DALAM INTERAKSI SISWA KELAS X DAN GURU PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI SMA (SLUA) SARASWATI 1 DENPASAR - Ni Ketut Sudianti; I Nengah Karsana; Kadek Dwi Sentana Putra; Ni Made Suyeni (Yayasan Pendidikan Literasi Borneo, 2026)
This study examines: (1) the actualization of Guru Bhakti teachings in interactions between tenth-grade students and teachers, (2) the obstacles encountered and efforts to overcome them, and (3) their impact on student attitudes and behavior at Saraswati 1 Senior High School (SLUA) Denpasar. This study aims to identify and describe the actualization of Guru Bhakti teachings in interactions between tenth-grade students and teachers in the subjects of Hindu Religious Education and Character Education. This study uses Carl Rogers' Humanistic Theory, Thomas Lickona's Character Education Theory, and George Herbert Mead and Herbert Blumer's Symbolic Interactionism Theory. The research subjects included the Vice Principal, the Hindu Religious Teacher, and tenth-grade students of Saraswati 1 Senior High School (SLUA) Denpasar. Data were collected through observation, in-depth interviews, documentation, and literature review, then analyzed using qualitative phenomenological methods. The results of the study indicate that the actualization of Guru Bhakti has been implemented well, both inside and outside of learning. This is seen through verbal interactions such as greetings, salutations, polite language, and the 3S culture, as well as nonverbal interactions in the form of attention, politeness, and respect for teachers. The obstacles faced come from internal factors, such as the psychological condition and awareness of students, as well as external factors, such as family environment, peers, and teacher character. Efforts made to overcome these include an individual approach, character development, role models, and habituation of respectful attitudes. The impact is seen in increased respect, discipline, responsibility, politeness, and self-control of students.